Performance improvement on LiFePO4/C composite cathode for lithium-ion batteries - Cech, Ondrej (2013)
Temperature glycine assisted solid-state synthesis was used to prepare LiFePO4/C composite samples with two types of material improvements. It will be shown how can addition of a high conductive support as well as doping with supervalent metal ions improve the electrochemical performance of Li-ion cathode. Three samples with different properties were prepared and investigated e pure LiFePO4/ C with no material improvements, LiFePO4/C prepared with multi walled carbon nanotubes (MWCNT) conductive support and LiFePO4/C doped by 1% of cobalt. Glycine was used as inorganic carbon coating precursor during the synthesis of all samples. XRD measurements confirmed production of highly crystalline LiFePO4 cathode material with diameter varying between 40 nm and 200 nm. Electrochemical measurements confirmed increasing the intra-particle conductivity by MWCNT or Co doping. Galvanostatic battery testing shows that LiFePO4/MWCNT/C composite delivers highest capacity 130 mA h g1 at C/5. LiFePO4/MWCNT/C cathode material prepared by solid state synthesis exhibit excellent electrochemical performances, improved conductivity, and good rate capability compared to the LiFePO4/C composite material.